2018
DOI: 10.1177/1477153517736804
|View full text |Cite
|
Sign up to set email alerts
|

A new procedure for determining the road surface reduced luminance coefficient table by on-site measurements

Abstract: Numerous measurements have shown that the standard R classes do not represent adequately many road surfaces used nowadays. Therefore, the construction of portable reflectometers intended for on-site measurements of road surface reflection properties has been given particular attention during the last decade. This paper presents a new procedure for the improvement of the accuracy of such a portable reflectometer. Optimally extrapolating the values of the 20 luminance coefficients (q), each measured by the porta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Studies show that the average luminance for dark asphalt can only be 30% of the value obtained for a light one [19]. Measurements could be performed in the field to determine the real reduced luminance coefficient [24][25][26], but this would mean closing the road to the traffic for an unacceptable time. Imaging measurements can also be used in order to calculate the reflectance properties of the asphalt, just as the authors have demonstrated in the paper [27].…”
Section: Case Study Regarding the Influence Of Longitudinal Observer Position In Luminance Measurementsmentioning
confidence: 99%
“…Studies show that the average luminance for dark asphalt can only be 30% of the value obtained for a light one [19]. Measurements could be performed in the field to determine the real reduced luminance coefficient [24][25][26], but this would mean closing the road to the traffic for an unacceptable time. Imaging measurements can also be used in order to calculate the reflectance properties of the asphalt, just as the authors have demonstrated in the paper [27].…”
Section: Case Study Regarding the Influence Of Longitudinal Observer Position In Luminance Measurementsmentioning
confidence: 99%
“…Following this, a number of methods have emerged for evaluating this parameter. Nevertheless, the evaluation of this criterion is complex and still requires an improvement of measurement methods [3]. CIE introduced the R classification system according to which each type of pavement is classified into one of four classes, from R1 to R4.…”
Section: Introductionmentioning
confidence: 99%
“…31 While these classification methods and specifications are still in use today, some measurements have indicated that the R and W classes do not represent adequately pavements currently used. 3235 To analyse the change of current pavement reflection properties and their impacts, some researchers have done meaningful works as follows. The SURFACE project conducted by European researchers provided a pre-normative guideline for road characterization including the aging and wet condition of pavement.…”
Section: Introductionmentioning
confidence: 99%